Workshop Pelatihan Learning Management System (LMS) Untuk Peningkatan Kualitas Pembelajaran Jarak Jauh Di SMP Negeri 242 Jakarta - Achmad Nur Hidayaht; Nandi Kurniawan; Nurul Istiqomah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This community service activity is to provide training in designing online learning through the use of the Edmodo online platform for teachers of SMP Negeri 242 Jakarta. This is due to the Covid-19 pandemic which requires learning activities to be carried out from home (PJJ). The ability of teachers to utilize digital learning platforms by moving offline learning to online learning, as well as organizing student assignments into competencies that must be mastered and improved in order to create synchronous and asynchronous learning. The application of Edmodo is a learning alternative that creates effective learning to support the process of organizing learning activities because Edmodo has several features, such as